A Terapia Comunitária como instrumento de inclusão da Saúde Mental na Atenção Básica: avaliação da satisfação dos usuários - Andrade, Fábia Barbosa de (2009)
The search for a democratic model of health woke up the government's attention for the establishment of priorities and strategies, that impelled the implantation of the Program of Health of the Family (PSF), now denominated Strategy Health of the Family (ESF), in order to approximate the team of the community's health and, like this, to implement actions of promotion of the health and of prevention of the disease. In that perspective the Community Therapy (TC) it emerges as a care technology returned to the mental health in the Basic Attention of Health. Since 2007, TC has been developed in the municipal district of João Pessoa/PB by professionals of ESF: nurses, community agents of health, doctors, odontólogos, physiotherapists, nutritionists, besides psychologists, among others. The present study had as objectives: to evaluate the users' satisfaction in relation to TC in the Basic Attention in the municipal district of João Pessoa/PB; to measure the level of the participants' of TC satisfaction in relation to that tool of the care; to identify important elements for the satisfaction in relation to TC on the part of the users; to discuss that way TC strengthens the care with the mental health in the Basic Attention of Health. It is a study evaluative, traverse and observational, accomplished in the period of May to August of 2009. It was used as instrument of collection of data the Scale of Evaluation of the Satisfaction of the Users with the Services of Mental Health - Satis- BR, as well as an instrument of complemented questions used by the community therapists. The results revealed that of the 198 (100%) interviewees, 105 (53%) they verbalized satisfaction and 93 (47%) a lot of satisfaction in the encounters of TC, what evidences that the totality of the sample is satisfied with the therapy. The important elements that competed for the users' of TC satisfaction they were: I respect, dignity, listens, understanding, reception, support in the needs and good facilities of the places where it happens the therapy. TC is strengthening the care to the mental health, for constituting as a prevention technology, reducing the psicofármacos consumption and strengthening the entrance door for the net of mental health and of support psychosocial. The implantation and the development of TC in the Basic Attention of Health consolidate the objectives of that therapy, once he/she intends to be a space of he/she listens, relief of the suffering and a technology of prevention of the mental disease. It is ended, therefore, that TC is highlighting if as instrument of inclusion of the mental health in the Basic Attention in the attendance to the users of the Unique System of Health.